Rotational Thromboelastometry: Enhancing Hemostasis Monitoring in Anesthesia - Girishkumar Modi; Vijay Kumar; Nagaraju Munagala (Research and Practice in Anesthesiology, 2023)
Rotational thromboelastometry (ROTEM) is a viscoelastic point-of-care coagulation test that measures the dynamics of clot formation and lysis in whole blood samples. A cylindrical shaft that oscillates while passing through a tiny amount of blood is used in the procedure. Blood exerts increasing pressure on the shaft as it thickens into a clot. We can track the strength of the forming clot over time by measuring this resistance. ROTEM® can provide valuable information about the coagulation status of patients who are at risk of bleeding or thrombosis in various peri-operative settings, such as trauma, obstetrics, cardiac surgery, liver transplantation, and major orthopedic and vascular surgeries. In addition, it can aid in the diagnosis and treatment of peri-operative coagulopathy, reduce unneeded transfusions, and enhance patient outcomes.